The Activity of the Durum Wheat (Triticum durum L.) Catalase 1 (TdCAT1) Is Modulated by Calmodulin - Mouna Ghorbel; Kaouthar Feki; Sana Tounsi; Najla Haddaji; Moez Hanin; Faiçal Brini (MDPI AG, 2022)
Plant catalases (CAT) are involved in the cellular scavenging of the reactive oxygen species during developmental processes and in response to abiotic and biotic stresses. However, little is known about the regulation of the CAT activity to ensure efficient antioxidant function. Using bioinformatic analyses, we showed that durum wheat catalase 1 (TdCAT1) harbors highly conserved cation-binding and calmodulin binding (CaMBD) domains which are localized at different positions of the protein. As a result, the catalytic activity of TdCAT1 is enhanced in vitro by the divalent cations Mn2+ and Fe2+ and to a lesser extent by Cu2+, Zn2+, and Mg2+. Moreover, the GST-pull down assays performed here revealed that TdCAT1 bind to the wheat CaM (TdCaM1.3) in a Ca2+-independent manner. Furthermore, the TdCaM1.3/Ca2+ complex is stimulated in a CaM-dose-dependent manner by the catalytic activity of TdCAT1, which is further increased in the presence of Mn2+ cations. The catalase activity of TdCAT1 is enhanced by various divalent cations and TdCaM1.3 in a Ca-dependent manner. Such effects are not reported so far and raise a possible role of CaM and cations in the function of CATs during cellular response to oxidative stress.